Association of Urinary Sodium Excretion and Left Ventricular Hypertrophy in People With Type 2 Diabetes Mellitus: A Cross-Sectional Study - Liu, Jianfang; Yang, Xiaoyu; Zhang, Peizhen; Guo, Dan; Xu, Bingyan; Huang, Chensihan; Xue, Yaoming; Zhang, Huijie (Frontiers in Endocrinology, 2021)
Background: It has been well documented that left ventricular hypertrophy (LVH) is highly associated with the incidence of cardiovascular disease (CVD). Evidence indicated that high sodium intake was closely related with LVH in general population. However, information is not available regarding the association between urinary sodium excretion and LVH in patients with type 2 diabetes mellitus (T2DM). This study aimed to explore the association between urinary sodium excretion and LVH in patients with T2DM. Methods: This cross-sectional analysis included baseline data from 1,556 individuals with T2DM enrolled in the NanFang Prospective Diabetes Study (NFPDS). Urinary sodium excretion levels were measured from 24-hour urine samples of inpatients and morning fasting urine samples of outpatients. Left ventricular dimensions were assessed by echocardiography. The associations between urinary sodium excretion and the risks of cardiovascular events, LVH and left ventricular mass index (LVMI) were examined using linear regression analysis, logistic regression and restricted cubic splines (RCS). Results: Urinary sodium excretion levels were positively associated with cardiometabolic risk factors, including systolic blood pressure, body mass index, waist circumference and LVMI (All P<0.001). Odds ratios of the highest quartile of urinary sodium excretion compared with the lowest quartile were 1.80 (95% CI, 1.28-2.54; P=0.001) for LVH and 1.77 (95% CI, 1.06-2.94; P=0.028) for CVD, after adjusted for demographics, lifestyle risk factors and cardiovascular risk factors. Multivariable-adjusted RCS analysis of the association between urinary sodium excretion and LVMI showed a significant association (P=0.001) and lacked evidence of a nonlinear association (P=0.406). Conclusion: This study indicated that high urinary sodium excretion was independently associated with increased risk of LVH and CVD in patients with T2DM, suggesting that control of sodium intake may be valuable for the prevention of diabetic cardiovascular complications.